Self‐supporting graphene films and their applications. Issue 6 (1st November 2015) - Goniszewski, Stefan; Gallop, John; Adabi, Mohammad; Gajewski, Krzysztof; Shaforost, Olena; Klein, Nobert; Sierakowski, Andzrej; Chen, Jie; Chen, Yifang; Gotszalk, Teodor; Hao, Ling
Abstract : Graphene, a self‐supporting monolayer, has excited enormous interest over the 10 years since its discovery due to its remarkable electrical, mechanical thermal and chemical properties. Here the authors describe the authors' work developing chemical vapour deposition methods to grow monolayer graphene on copper foil substrates and the subsequent transfer process. Raman microscopy, scanning electron microscopy and atomic force microscopy are used to examine the quality of the transferred material. To demonstrate the process, they also describe transfer onto patterned SiO2 /Si substrate which forms free suspended graphene drums. These show interesting mechanical properties which are being explored as nanomechanical resonators.